Adolescent's Willingness to Adopt a More Plant-Based Diet: A Theory-Based Interview Study - Havermans, Remco C.; Rutten, Geert; Bartelet, Dimona (Frontiers in Nutrition, 2021)
A plant-based diet is more sustainable, and research suggests that adolescents obtain health benefits from adopting a more plant-based diet (e.g., improved weight control, increased cardiovascular health). However, it is still unclear what factors promote/hinder their intention to attain such a dietary habit. The aim of the present study was to examine factors affecting adolescents' willingness to consume more plant-based foods. In a theory-based interview study, using the Reasoned Action Approach as framework, adolescents were interviewed concerning their reasons for their (un)willingness to adopt a more plant-based diet. A total of 11 adolescents (15/16 years old; 7 girls, 4 boys) were recruited and interviewed at two secondary schools in the Dutch Province of Limburg, the Netherlands. None of the interviewees reported being vegan/vegetarian/flexitarian. The interviewed adolescents overall expressed little interest in adopting a more plant-based diet. They appeared to have little knowledge of what would comprise a more plant-based diet and showed a lack of awareness of the benefits for personal and planet health. Further, most participants indicated lacking skills to prepare plant-based meals. Despite that, they felt confident they would be able to consume a much more plant-based diet for a definite period. Most importantly, the low intention to consume more plant-based food options was explained by the perceived (or expected) poor taste of these foods. We conclude that education on the plant-based diet (i.e., increasing awareness of the benefits, and skills to procure or prepare a plant-based meal) might increase both knowledge and plant-based food familiarity. The latter being important as food familiarity is key in promoting its acceptance.